Hubungan antara Tipe Kepribadian Big-Five dengan Gambling Disorder pada Pemain Judi Online - Riki Agung Sonjaya; Fanni Putri Diantina (UPT Publikasi Ilmiah Unisba, 2024)
Abstract. Gambling is a form of gaming that involves a certain amount of money. Gambling in the current era is growing rapidly where there are lots of sites that provide various types. Gambling that is currently popular is online slot gambling. This gambling causes addictive behavior, uncontrolled gambling behavior can become a problem. This personality greatly influences a person's addiction, nature and personality are one of the factors that can influence a person's addiction. Therefore, this research aims to see the relationship between the Big Five personality theory and Gambling Disorder in online slot gambling players. The instruments used in this research were the Big Five Inventory-2 (BFI-2) developed by Soto & John (2017) and adapted to the Indonesian version by Ahya & Siaputra (2021) and the Problem Gambling Severity Index (PGSI) developed by Ferris & Wynne (2001). This research data was obtained from 280 respondents selected using purposive sampling techniques. This research method uses a correlational method with Spearman rank test analysis. The research results show that the Openness aspect has a significant positive correlation with gambling disorders of (0.495), the Conscientiousness aspect has a significant positive correlation of (0.522), the Extraversion aspect has a significant positive correlation of (0.148), the Agreeableness aspect has a significant positive correlation of (0.148) a significant positive correlation of (0.227), and the Neuroticism aspect has a significant positive correlation. positive (0.596). Abstrak. Gambling merupakan sebuah bentuk permainan yang melibatkan sejumlah uang, perjudian di era sekarang berkembang pesat dimana banyak situs-situs yang menyediakan beragam jenisnya, perjudian yang sedang marak saat ini yaitu judi slot online. Perjudian ini menimbulkan perilaku kecanduan, perilaku berjudi yang tidak terkendali dapat menjadi masalah (problematic). Kepribadian ini sangat mempengaruhi dari kecanduan seseorang, sifat dan kepribadian adalah salah satu faktor yang dapat berpengaruh terhadap kecanduan dari individu. Karena itu, penelitian ini bertujuan untuk melihat hubungan antara Teori kepribadian Big Five dan Gambling Disorder pada pemain judi slot online. Instrumen yang digunakan dalam penelitian ini adalah Big Five Inventory-2 (BFI-2) yang dikembangkan oleh Soto & John (2017) dan diadaptasi ke versi bahasa Indonesia oleh Ahya & Siaputra (2021) dan Problem Gambling Severity Index (PGSI) yang dikembangkan oleh Ferris & Wynne (2001). Data penelitian ini diperoleh dari 280 responden yang dipilih menggunakan teknik purposive sampling. Metode penelitian ini menggunakan metode korelasional dengan analisis uji rank spearman. Hasil menunjukan aspek Openness signifikan berkorelasi positif terhadap gambling disorder sebesar (0,495), aspek Conscientiousness signifikan berkorelasi positif sebesar (0,522), aspek Extraversion signifikan berkorelasi positif sebesar (0,148), aspek Agreeableness signifikan berkorelasi positif sebesar (0,227), dan aspek Neuroticism signifikan berkorelasi positif sebesar (0,596).